2009
DOI: 10.1590/s0102-311x2009000200020
|View full text |Cite
|
Sign up to set email alerts
|

Perfil nutricional e fatores associados à ocorrência de desnutrição entre crianças indígenas Kaingáng da Terra Indígena de Mangueirinha, Paraná, Brasil

Abstract: The goal of this study was to evaluate the nutritional status of indigenous children and to investigate factors associated with nutritional deficits. Weight and height measurements were obtained for 141 Kaingáng children from 0 to 5 years of age living on the Mangueirinha Indigenous Reserve in Paraná State, Brazil. Data on maternal and infant conditions and socioeconomic characteristics were also gathered through face-to-face interviews. Based on World Health Organization criteria (2006), 24.8% of the children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1
30

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 31 publications
4
13
1
30
Order By: Relevance
“…However, although reports of malnutrition, in general, characterise children's anthropometric profiles among indigenous peoples, the increase in children with obesity in this population merits particular attention. Evaluating the nutritional status of indigenous children from Alto Xingu, and in a study of the nutritional profile of indigenous Kaingáng children, Mondini et al 34 and Kuhl et al 35 , respectively, also found a marked percentage of overweight, similar to that observed in this study. The authors also noted that these findings are not isolated cases in the indigenous context and note that recent studies have identified cases of overweight amongst children from different indigenous groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, although reports of malnutrition, in general, characterise children's anthropometric profiles among indigenous peoples, the increase in children with obesity in this population merits particular attention. Evaluating the nutritional status of indigenous children from Alto Xingu, and in a study of the nutritional profile of indigenous Kaingáng children, Mondini et al 34 and Kuhl et al 35 , respectively, also found a marked percentage of overweight, similar to that observed in this study. The authors also noted that these findings are not isolated cases in the indigenous context and note that recent studies have identified cases of overweight amongst children from different indigenous groups.…”
Section: Discussionsupporting
confidence: 87%
“…Living conditions are unequal between Brazilian indigenous and non-indigenous families, particularly in access to running water, basic sanitation, and solid waste management 27 . According to Kühl et al 14 , in indigenous communities the use of non-durable building materials does not necessarily mean lower socioeconomic status and should not be interpreted immediately as such, but only after careful analysis of the local context. However, the authors highlight that in the specific context of the Kaingang from the Mangueirinha Indigenous Land in Paraná State, the materials used to build walls in the homes could in fact be used as a proxy for socioeconomic status 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate and severity of cardiovascular diseases, including arterial hypertension, are higher among indigenous peoples 13 and thus have a greater impact on mortality 12 . Among the Kaingang people, despite a growing body of literature on their health conditions 14,15 , there is little research on hypertension. Thus, the increasing rates of NCDs among indigenous peoples in Brazil and the new demands placed on healthcare services highlight the relevance of studies on their epidemiological profile in order for the resulting data to orient healthcare planning and services.…”
Section: Introductionmentioning
confidence: 99%
“…Este aspecto é preocupante e fere uma das diretrizes do PNAE 3 , que é de garantir o emprego de alimentação saudável e adequada nos espaços escolares. De fato, estudos diversos, realizados com etnias indígenas distintas, têm apontado elevadas prevalências de excesso de peso/obesidade na infância e adolescência indí-gena 20,29,30,31,32 . Na literatura, aponta-se, como possíveis fatores explicativos desse aumento de peso entre os indígenas, a ocidentalização de dietas indígenas, caracterizadas por maior consumo de alimentos industrializados (com elevado teor de sódio, açúcar e gorduras) em detrimento do consumo de alimentos tradicionais 20,29,33,34,35 .…”
Section: Grupos De Alimentosunclassified
“…De fato, estudos diversos, realizados com etnias indígenas distintas, têm apontado elevadas prevalências de excesso de peso/obesidade na infância e adolescência indí-gena 20,29,30,31,32 . Na literatura, aponta-se, como possíveis fatores explicativos desse aumento de peso entre os indígenas, a ocidentalização de dietas indígenas, caracterizadas por maior consumo de alimentos industrializados (com elevado teor de sódio, açúcar e gorduras) em detrimento do consumo de alimentos tradicionais 20,29,33,34,35 . Pesquisas conduzidas no mesmo período e nas mesmas escolas a que se refere o presente estudo apontaram, além de prevalências expressivas de valores inferiores a -2 escores-z para o índice estatura/idade entre crianças (15,5%) e adolescentes (19,9%), percentual crescente do excesso de peso, desde a infância até a vida adulta 36 , mensurados por indicadores que avaliam a adequação do peso em relação à estatura.…”
Section: Grupos De Alimentosunclassified